LITERASI NUMERASI PESERTA DIDIK DALAM MENYELESAIKAN SOAL TEOREMA PYTHAGORAS DI MTS NEGERI 2 PONTIANAK - Dzulhizza, Siti; Mirza, Ade; Fitriawan, Dona (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study was conducted with the aim of describing the numeracy literacy of students with above-average and below-average abilities in solving problems related to the Pythagorean Theorem. The method used was descriptive qualitative, with data collection techniques involving a numeracy literacy test and interview guidelines. The research subjects consisted of 35 eighth-grade students at MTs Negeri 2 Pontianak. Out of the 35 students, 4 were selected based on the results of the numeracy literacy test and daily assessment scores to be interviewed in order to gain deeper insights into their responses on the given test. The results of the study showed that students with above-average abilities were able to fulfill two to three numeracy literacy indicators. These students were capable of using symbols or numbers, analyzing the information in the questions, and drawing conclusions from the results obtained, although there were some miscalculations. On the other hand, students with below-average abilities were less able to meet all numeracy literacy indicators. They had difficulty using symbols,and made errors in analyzing information and drawing conclusions.